2015
DOI: 10.1016/j.bone.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A phase I feasibility study of multi-modality imaging assessing rapid expansion of marrow fat and decreased bone mineral density in cancer patients

Abstract: Purpose Cancer survivors are at an increased risk for fractures, but lack of effective and economical biomarkers limits quantitative assessments of marrow fat (MF), bone mineral density (BMD) and their relation in response to cytotoxic cancer treatment. We report dual energy CT (DECT) imaging, commonly used for cancer diagnosis, treatment and surveillance, as a novel biomarker of MF and BMD. Methods We validated DECT in pre-clinical and Phase I clinical trials and verified with water-fat MRI (WF-MRI), quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
3
27
1
6
Order By: Relevance
“…A number of imaging studies have been published to estimate RM and YM (2023). In a clinical study, we previously reported water-fat magnetic resonance imaging (WF-MRI) to visualize and map marrow compositions and its high correlation with DECT derived marrow fat measurements (16,24). Due to technical difficulties, lengthy scanning time, and cost, the use of WF-MRI is mainly confined to small skeletal regions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of imaging studies have been published to estimate RM and YM (2023). In a clinical study, we previously reported water-fat magnetic resonance imaging (WF-MRI) to visualize and map marrow compositions and its high correlation with DECT derived marrow fat measurements (16,24). Due to technical difficulties, lengthy scanning time, and cost, the use of WF-MRI is mainly confined to small skeletal regions.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the patients undergoing HCT receive prior chemotherapy treatment. Because cancer treatment changes marrow fat composition, (16) individual factors including age and prior treatment may influence the distribution of marrow composition in different sites. Thus, if treatment is developed for differential radiation delivery to individual marrow composition, it will have to be individualized ( personalized medicine).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations